AL-MAQQAHID AL-SHARI’AH PHILOSOPHICAL ASPECTS AND ITS RELEVANCE TO CONTEMPORARY IJTIHAD - Darma, Andi Moh. Rezki; Musyahid, Achmad; Jamaluddin, Samsidar (International Journal of Social Science, 2022)
This study aims to describe maqashid al-Syariah in terms of the philosophical aspects of maqashid al-Syariah, the relevance of maqashid al-Syariah with contemporary ijtihad. This research uses descriptive qualitative. Data were collected through interviews, observation, and documentation. This study uses data analysis techniques, which consist of stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the research on the relevance of maqashid al-Shariah with contemporary ijtihad show the philosophy of maqashid al-Syariah. Contemporary ijtihad also tries to see significant changes in Islamic law from time to time, namely changes from the family aspect, women's aspect, and worship aspect. In an effort to develop Islamic legal thought, especially in providing understanding and clarity on various contemporary legal issues, mujtahids need to know the purpose of Islamic law. In addition, the purpose of the law needs to be known in order to identify whether a legal provision can still be applied to a particular case or because of changes in social structure, the law can no longer be maintained. Thus, knowledge of Maqāṣid al-Shari'ah is the key to the success of the mujtahid in his ijtihad.